1998
DOI: 10.1098/rspb.1998.0407
|View full text |Cite
|
Sign up to set email alerts
|

The fate of cetacean carcasses in the deep sea: observations on consumption rates and succession of scavenging species in the abyssal north-east Atlantic Ocean

Abstract: The fate of cetacean carcasses in the deep sea was investigated using autonomous deep-sea lander vehicles incorporating time-lapse camera systems, ¢sh and amphipod traps. Three lander deployments placed cetacean carcasses at depths of 4000^4800 m in the northeast Atlantic for periods of 36 h, 152 h and 276 h before being recovered. The photographic sequences revealed that carcasses were rapidly consumed by ¢sh and invertebrate scavengers with removal rates ranging from 0.05^0.4 kg h 71. In the longest experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
84
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 40 publications
5
84
0
Order By: Relevance
“…Lampitt et al (1986) showed a logarithmic decline in megabenthos biomass from 800 to 4100 m in the PSB, which is a proxy for predator food availability. The distribution of carrion is not so well described (Stockton & Delacca 1982;Jones et al 1998;Smith & Baco 2003), but is likely to decline with distance from shore and hence, usually with depth. Consequently, the relative selective pressures for swimming speed, nutrient storage and metabolic economy will differ greatly between scavengers and non-scavengers, even when these species are closely related (note that the four species of Coryphaenoides show positive, negative and no relationship with depth; figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Lampitt et al (1986) showed a logarithmic decline in megabenthos biomass from 800 to 4100 m in the PSB, which is a proxy for predator food availability. The distribution of carrion is not so well described (Stockton & Delacca 1982;Jones et al 1998;Smith & Baco 2003), but is likely to decline with distance from shore and hence, usually with depth. Consequently, the relative selective pressures for swimming speed, nutrient storage and metabolic economy will differ greatly between scavengers and non-scavengers, even when these species are closely related (note that the four species of Coryphaenoides show positive, negative and no relationship with depth; figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…These hypotheses are supported by recent studies of small marine vertebrate remains. Two porpoises and a dolphin, weighing between 50 and 100 kg and placed directly on the seabed at 4800 m in the Porcupine Abssyal Plain were studied over a period of 1-12 days by time-lapse camera ( Jones et al 1998). Although the duration of the experiment was almost certainly too short for Osedax to have had time to settle, the limited skeletal remains after just 12 days on the seabed, and the likelihood of many of the small bones being scavenged or settling into the sediment, suggests that there would be little available bone material left after three to four weeks.…”
mentioning
confidence: 99%
“…However, previous studies have sought to investigate the response of scavengers in the deep sea to food falls, in the form of animal carcasses, rich in protein and lipids, or plant and algal material comprised of protein and carbohydrates (Gooday and Turley 1990;Klages et al 2002;Jones et al 1998;Priede et al 1994). There are currently two approaches to studying these food falls.…”
Section: Discussionmentioning
confidence: 99%